2006
DOI: 10.1248/cpb.54.252
|View full text |Cite
|
Sign up to set email alerts
|

Rossicasins A, B and Rosicaside F, Three New Phenylpropanoid Glycosides from Boschniakia rossica

Abstract: Boschniakia rossica (CHAM. et SCHLECH.) FEDTSCH. et FLEROV. (Orobanchaceae) is a parasitic plant growing on the root of plants of the genus Alnus (Betulaceae), as a substitute for Cistanchis Herba, a famous staminal tonic agent.1) The crude extracts of B. rossica showed a variety of pharmacological activities including antitumor, 2) anti-inflammatory, 2) antisenile, 3) antioxidative, and free radical scavenging activities.4) Previous chemical studies of B. rossica have led to the isolation of a number of pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…15,16) Various plants used in traditional medicine contain significant amounts of iridoid glucosides. [8][9][10]21,22) Some iridoid and phenylpropanoid compounds have rencently been isolated from Boschniakia rossica and presumed to be responsible for its major pharmacological function. [5][6][7]21) The present in vivo study has demonstrated the hepatoprotective potential of the iridoid compounds from Boschniakia rossica.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16) Various plants used in traditional medicine contain significant amounts of iridoid glucosides. [8][9][10]21,22) Some iridoid and phenylpropanoid compounds have rencently been isolated from Boschniakia rossica and presumed to be responsible for its major pharmacological function. [5][6][7]21) The present in vivo study has demonstrated the hepatoprotective potential of the iridoid compounds from Boschniakia rossica.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The chemical constituents of Boschniakia rossica were also investigated, which led to the isolation of several phenylpropanoid and iridoid compounds. [8][9][10] Based on the data from our laboratory and others, we have suggested that iridoid compounds from Boschniakia rossica may be effective in protecting the liver against acute CCl 4 toxicity. So far, however, there has been little research reported on the in vivo hepatoprotective effect of iridoid compounds from Boschniakia rossica.…”
mentioning
confidence: 92%
“…Ninety three compounds 163 – 254 [5,19,21,24,37,46,51,55,63,64,65,66,67,75,78,79,80,81,82,83,84,85,86,93,94,95,96,97,98,99,100,101,102,103,104] represent the trisaccharide ester category. They are mainly obtained from the Scrophulariaccae plant family.…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…The anomeric carbon configuration of glucose unit in ligupurpuroside F ( 234 ) is not determined [24]. Rossicaside F ( 254 ) exists as epimers at the β-C of the phenethyl alcohol moiety ( R , S -β- O Et) [98].…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…In this group, all oligosaccharide esters consist of three monosaccharides including glucopyranose, fructofuranose, and rhamnopyranose with O -substituents, which comprise feruloyl, sinapoyl, and 3,4,5-trimethoxycinnamoyl groups. Oligosaccharide esters ( 146 – 149 ) listed in Table 4 as well as kankanose ( 150 ), cistantubulose A 1 /A 2 ( 151 ), cistansinensose A 1 /A 2 ( 152 ), and compound 153 shown in Figure 5 have been found in the roots of Polygala tricornis [ 37 ], the stems of Cistanche tubulosa [ 81 , 87 ] and C. sinensis [ 80 ], the whole parts of Boschniakia rossica [ 88 ], and the rhizomes of Iris brevicaulis [ 89 ].…”
Section: Chemical Structuresmentioning
confidence: 99%